Elevated D-Dimer levels correlate with the development of hepatorenal syndrome and a poor outcome in patients with cirrhosis. (2nd December 2022) - Chen, Baode; Liu, Jing; Li, Yongtao; He, Xuelin; Zhou, Cheng; Chen, Yu; Zheng, Min
Abstract: Objectives: Whether hemostatic status was correlated with the diverse types of acute kidney injury in cirrhotic patients is unclear. The present study aimed to investigate the relationship between hemostatic markers and the diverse types of acute kidney injury (AKI) in liver cirrhosis. Patients and methods: Cirrhotic patients with consecutive treatment at the First Affiliated Hospital of Medicine School, Zhejiang University, were pooled in a cohort. Their demographic and clinical data, biochemistry parameters and hemostatic markers were assessed to identify risk factors for the development and prognosis of AKI. Results: A total of 773 cirrhotic patients were included in this cohort. Patients with hepatorenal syndrome (HRS) had significantly higher D-Dimer than those with the other types of AKI. In univariate COX regression, APTT, TT, INR, D-Dimer and Fib were correlated with the development of AKI, HRS and acute tubular necrosis (ATN), however, only D-Dimer remained independently associated with the development of AKI and HRS in multivariate COX regression. The area under the ROC curve of D-Dimer was 0.755 (95%CI, 0.718–0.793) in predicting the development of AKI, 0.879 (95%CI, 0.791–0.967) in predicting the development of HRS, respectively. D-Dimer was used for diagnosis of HRS with a sensitivity of 87.3% and specificity of 72.9% at the cutoff of 3.7 (mg/L FEU). Survival rates differed significantly between groups by D-Dimer level. Conclusions: Hemostatic markers were significantly associated with the diverse types of AKI. D-Dimer was an independent risk factor for HRS and correlated with a poor outcome in cirrhotic patients.